2023
DOI: 10.1111/pai.13941
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and anxiety development in Australian children and adolescents

Abstract: Background Evidence has suggested a bidirectional association between both the effects and onset of asthma and anxiety. The direction of this association in children and adolescents is less clear. The study evaluates whether anxiety in children is associated with the development of later asthma or, by contrast, whether asthma in children precedes anxiety. Methods Parental reports from 9369 children at two age points (4–5 and 14–15 years old) and from baby (B) (recruited at birth in 2004) and kindergarten (K) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…In particular, accumulating studies have indicated that asthma with a childhood-onset is associated with increased risk of severe mental illnesses in later life. Meta-analyses of observational studies have reported children with asthma had higher risk of developing subsequent major depressive disorder (MDD) [3,4], bipolar disorder [4,5], schizophrenia [5], anxiety [6], autism [7]and attention deficit hyperreactivity disorder (ADHD) [8,9]. While various covariates have been controlled in these studies, the remaining uncontrolled confounding factors and reverse causation bias still limit the ability of elucidating the causal relationships from observational studies [10].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, accumulating studies have indicated that asthma with a childhood-onset is associated with increased risk of severe mental illnesses in later life. Meta-analyses of observational studies have reported children with asthma had higher risk of developing subsequent major depressive disorder (MDD) [3,4], bipolar disorder [4,5], schizophrenia [5], anxiety [6], autism [7]and attention deficit hyperreactivity disorder (ADHD) [8,9]. While various covariates have been controlled in these studies, the remaining uncontrolled confounding factors and reverse causation bias still limit the ability of elucidating the causal relationships from observational studies [10].…”
Section: Introductionmentioning
confidence: 99%
“…The results of Garcia‐Sanchez et al's study 5 could raise health professionals' awareness of the increased risk of developing anxiety among children and adolescents with asthma. Clinicians should formulate strategies to assess anxiety in young patients with asthma and offer psychological support to either prevent the increased risk of and/or reduce the burden of anxiety symptoms.…”
mentioning
confidence: 96%
“…The study of Garcia‐Sanchez et al 5 is therefore particularly relevant, since it used a longitudinal and representative sample from two cohorts of Australian children to assess whether anxiety in adolescents was associated with the occurrence of asthma in childhood or, conversely, if anxiety in children precedes asthma in adolescence.…”
mentioning
confidence: 99%
“…Consequently, asthma is regarded as one of the leading causes of school absenteeism and is associated with poorer academic performance and reduced quality of life. 3,4 If not appropriately managed, pediatric asthma can result in reduced lung function and greater respiratory events throughout adulthood, 5 which subsequently increases the risk of early-onset comorbidities and premature mortality. 6 As such, the prevention and management of pediatric asthma has become a global priority, with increased interest in understanding and characterizing the natural disease progression.Wheezing is the primary clinical manifestation of asthma and often originates in early life, with up to 50% of children wheezing during their preschool years (before age 6).…”
mentioning
confidence: 99%